Acute heart failure and bradyarrhythmia in a young male—what hides beneath the surface?: a case report. Issue 10 (9th October 2021) - Santos, João; Almeida, Inês; Pires, Inês; Blanco, Filipe
Abstract: Background: Muscular dystrophies (MDs) are characterized by early-onset muscular atrophy and weakness, with frequent cardiac involvement. Myocardial dysfunction and conduction system involvement are often rapidly progressive despite medical and device therapy, and may even precede muscular symptoms, posing a challenge to diagnosis. Case summary: We report a case of a young male admitted to a cardiac intensive care unit due to ' de novo ' acute heart failure (HF) and atrial flutter with a slow ventricular response. Careful evaluation of past medical history revealed the presence of neuromuscular symptoms since childhood, disregarded throughout adult age. Diagnostic workup allowed to establish a diagnosis of non-dilated hypokinetic cardiomyopathy secondary to Emery-Dreifuss MD, due to lamin A/C (LMNA) gene mutation. Our patient was treated with neurohormonal modulation therapy and a cardiac resynchronization therapy defibrillator (CRT-D) was implanted, but due to worsening advanced HF, cardiac transplantation was needed. Discussion: Association of skeletal muscle and cardiac symptoms should always raise the suspicion for an underlying MD, since the consequences of a missed diagnosis are often dramatic. A timely diagnosis is crucial to prevent sudden death due to arrhythmias in these patients and to delay the progressive course of cardiomyopathy.